2023
DOI: 10.3390/ijms24043426
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Propidium Monoazide-Based Viability Quantitative PCR Assay for Red Sea Bream Iridovirus Detection

Abstract: Red sea bream iridovirus (RSIV) is an important aquatic virus that causes high mortality in marine fish. RSIV infection mainly spreads through horizontal transmission via seawater, and its early detection could help prevent disease outbreaks. Although quantitative PCR (qPCR) is a sensitive and rapid method for detecting RSIV, it cannot differentiate between infectious and inactive viruses. Here, we aimed to develop a viability qPCR assay based on propidium monoazide (PMAxx), which is a photoactive dye that pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…To address these points, a sample pre-treatment with DNA intercalants such as PMA and its derivatives (i.e., PMAxx) has been proposed to distinguish between infectious and non-infectious viruses. Recent studies have demonstrated the selective detection of various viruses using PMA, including norovirus, enterovirus, African swine fever viruses, and Red Sea Bream Iridovirus [ 20 , 21 , 22 , 23 ]. Recently, Hong et al [ 18 ] conducted in vitro experiments by inactivating or not inactivating the SARS-CoV-2 with UV light and using sodium dodecyl sulfate as a mild membrane destabilizer to increase the PMA permeability [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these points, a sample pre-treatment with DNA intercalants such as PMA and its derivatives (i.e., PMAxx) has been proposed to distinguish between infectious and non-infectious viruses. Recent studies have demonstrated the selective detection of various viruses using PMA, including norovirus, enterovirus, African swine fever viruses, and Red Sea Bream Iridovirus [ 20 , 21 , 22 , 23 ]. Recently, Hong et al [ 18 ] conducted in vitro experiments by inactivating or not inactivating the SARS-CoV-2 with UV light and using sodium dodecyl sulfate as a mild membrane destabilizer to increase the PMA permeability [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, only genomes from intact virions will be amplified and detected, while free nucleic acids or those from non-infectious viruses are not considered by a PCR. Initially, this test was primarily used to assess the integrity of bacterial pathogens [ 19 ]; however, it has since been applied to numerous viruses [ 16 , 17 , 18 , 20 , 21 , 22 , 23 ]. With the emergence of SARS-CoV-2, the question has arisen as to whether the use of PMA can aid in identifying viruses capable of infecting and producing new viral progeny from viral remnants or incomplete viruses and free viral genomes, particularly in samples that test positive by molecular assays but have low viral loads and stay positive for prolonged periods.…”
Section: Introductionmentioning
confidence: 99%
“…RSIV has been reported to survive in seawater at 25 °C and 15 °C for approximately 7–10 days [ 42 ]. To investigate the dynamics of RSIV in aquaculture settings, disease progression can be monitored through qPCR or histopathological analysis of fish.…”
Section: Discussionmentioning
confidence: 99%
“…Bound viral DNA inhibits qPCR amplification, providing a mechanism to effectively differentiate infectious and inactive viruses. Furthermore, this non-invasive method will aid in establishing a disease prediction system and epidemiological analysis using seawater [9].…”
Section: Introductionmentioning
confidence: 99%